Single Umbilical Stoma for Bilateral Ureterostomy after Radical Cystectomy - Basiri, Abbas; Soltani, Mohammad Hossein; Shakhssalim, Nasser; Shemshaki, Hamid Reza; Rezvani, Pouria; Bonakdar Hashemi, Milad (Urology Journal, 2021)
Purpose: Cutaneous ureterostomy after radical cystectomy is less preferred compared with other permanent urinary diversions due to bilateral stomas. Single umbilical stoma for bilateral ureterostomy (SUSBU) may be a choice, in this study we reviewed the outcomes of SUSBU in seventeen patients who underwent radical cystectomy. Methods and Materials: This was a case-series study conducted from April 2016 to Dec 2017. Seventeen male patients with confirmed PT2 bladder urothelial carcinoma who were not suitable for performing conduit or orthotopic urinary diversion, including those with high-risk patients underwent single umbilical stoma for bilateral ureterostomy after radical cystectomy. All patients were prospectively followed up for 24 months ± 2 months, this study was done in a teaching center mainly by senior residents. Results: The mean age of patients was 68.6 ± 6.41 years. The mean length of operation time was 176.7 ± 15.1 minutes (from intubation to extubation from anesthesia). Sixteen patients were diagnosed with PT2 and one patient had a PT4 diagnosis. The decrease in hemoglobin level after surgery was 1.72 mg/dl ± 0.35 and creatinine increased by 0.15 ± 0.05 mg/dl. None of our patients had oliguria. One case developed constipation and no gas passing, with the suspicion of obstruction, underwent abdominal exploration, however, no obstruction or urine leakage was found and the patient was treated conservatively. One patient developed a fever during admission, in which atelectasis was identified as the cause. One patient underwent a second operation because of fascia dehiscence. Conclusion: It seems that this technique is suitable for high-risk patients with acceptable operating time, surgical complications, and fast recovery after the operation and one ureterostomy bag instead of two one’s comparing to bilateral cutaneous ureterostomy.